2021
DOI: 10.21307/jofnem-2021-069
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular characterization of Filenchus pseudodiscus n. sp. from east Golestan province, north Iran; with an updated phylogeny of Malenchus Andrássy, 1968 (Tylenchomorpha: Tylenchidae)

Abstract: During a survey in Golestan province, north Iran, two populations belonging to the family Tylenchidae were recovered in association with Quercus sp., and a rotten wood sample of an unidentified forest tree. The first recovered species was mainly characterized by having a disc-like differentiation in the frontal end under the light microscope (LM), proposing it as a tentative member of the genus Discotylenchus. Detailed morphological studies using scanning electron microscope (SEM), however, did not reveal a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…These sequences and additional Tylenchidae DNA sequences from GenBank were used for phylogenetic analysis. The selection of outgroup taxa for each dataset were based on previously published studies [34][35][36][37]. Multiple nucleotide sequence alignments for the different genes were performed using the heuristics progressive method FFT-NS-2 algorithm of MAFFT v.7.450 [38].…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…These sequences and additional Tylenchidae DNA sequences from GenBank were used for phylogenetic analysis. The selection of outgroup taxa for each dataset were based on previously published studies [34][35][36][37]. Multiple nucleotide sequence alignments for the different genes were performed using the heuristics progressive method FFT-NS-2 algorithm of MAFFT v.7.450 [38].…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…In the 28S tree, members of subfamily Tylenchinae Örley [1] did not form a monophyletic group; species of Filenchus, Discotylenchus Siddiqi [73], Malenchus Andrássy [74], and Miculenchus Andrássy [75] were independently grouped at various positions of the tree. However, the Canadian population of F. vulgaris formed a clade with the sequences of F. vulgaris from the NCBI database and a few other species of Filenchus (namely, F. pseudodiscus Mortatazavi, Heydari, Abolafia, Castillo, and Pedram [37], F. aquilonius Wu [20], F. annulatus (Siddiqui and Khan) Siddiqi [22,69], F. hamuliger Brzeski [67] Tylenchus Bastian [76], and Malenchus as well. The tree also revealed that the sequence of Filenchus sp.…”
Section: Mz959285-mz959286 For C Acceptus; Mz959287-mz959288 For F Vulgaris)mentioning
confidence: 99%
“…SEM has a pivotal role in taxonomic studies of Tylenchidae. In recent studies, the identities of several genera and species have been clarified using this information (e.g., Panahandeh et al ., 2018 ; Qing and Bert, 2018 ; Panahandeh et al ., 2019a , 2019b , 2019c ; Gharahkhani et al ., 2020 ; Mortazavi et al ., 2021 ). The present SEM observations revealed that the cephalic region pattern of the two studied species is in agreement with the data presented by Brzeski and Sauer (1982) and the type VI of cephalic region pattern of Tylenchidae depicted by Geraert and Raski (1987) and Qing and Bert (2018) , i.e., the cephalic papillae are large and the amphidial openings are oblique slits.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analysis. The obtained sequences of 28S-rRNA and ITS-rRNA were aligned using ClustalX 1.83 (Thompson et al, 1997) along with the corresponding comparable sequence datasets of genetically close species within the genus Filenchus and other related genera published in GenBank (Atighi et al, 2013;Mortazavi et al, 2021;Munawar et al, 2021;Panahandeh et al, 2019). Neothada cancellata and Basiria bhabi were used as the outgroup taxa for 28S-rRNA and ITS-rRNA sequence datasets, respectively.…”
Section: Molecular Characterizationmentioning
confidence: 99%
“…Members of this group are normally represented in any given soil sample, and are more dominant in soils rich in algae and mosses (Ferris and Bongers, 2006;Siddiqi, 2000;Yeates and Bird, 1994). Currently, the family comprises 414 nominal species belonging to 44 genera (Mortazavi et al, 2021;Panahandeh et al, 2019;Qing and Bert, 2019). This group is characterized by several ancestral characters such as weak feeding apparatus, undifferentiated non-muscular corpus and the filiform tails (Siddiqi, 2000).…”
mentioning
confidence: 99%